2014
DOI: 10.1111/cns.12347
|View full text |Cite
|
Sign up to set email alerts
|

Brivaracetam Differentially Affects Voltage‐Gated Sodium Currents Without Impairing Sustained Repetitive Firing in Neurons

Abstract: AimsBrivaracetam (BRV) is an antiepileptic drug in Phase III clinical development. BRV binds to synaptic vesicle 2A (SV2A) protein and is also suggested to inhibit voltage-gated sodium channels (VGSCs). To evaluate whether the effect of BRV on VGSCs represents a relevant mechanism participating in its antiepileptic properties, we explored the pharmacology of BRV on VGSCs in different cell systems and tested its efficacy at reducing the sustained repetitive firing (SRF).MethodsBrivaracetam investigations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
(69 reference statements)
2
32
0
2
Order By: Relevance
“…Indeed, a well‐known feature of AEDs with a primary mechanism of action on voltage‐gated sodium channels is an efficient inhibition of sustained repetitive firing. However, additional studies with BRV in this experimental paradigm, even at supratherapeutic concentrations, showed BRV to be ineffective in reducing the neuronal firing (Table ) . This later study confirmed that minor inhibition of the transient currents of voltage‐gated sodium channels by BRV does not appear to translate into physiologically relevant effects on the intrinsic firing properties of neurons .…”
Section: Mechanism Of Actionsupporting
confidence: 53%
“…Indeed, a well‐known feature of AEDs with a primary mechanism of action on voltage‐gated sodium channels is an efficient inhibition of sustained repetitive firing. However, additional studies with BRV in this experimental paradigm, even at supratherapeutic concentrations, showed BRV to be ineffective in reducing the neuronal firing (Table ) . This later study confirmed that minor inhibition of the transient currents of voltage‐gated sodium channels by BRV does not appear to translate into physiologically relevant effects on the intrinsic firing properties of neurons .…”
Section: Mechanism Of Actionsupporting
confidence: 53%
“…Compound A showed potent activity on recombinant Kv1.1/Kvβ1 channels which prompted us to further validate the effects of the ligand on sustained repetitive firing in hippocampal slices from adult rats. The increase of the intrinsic excitability of neurons, leading to sustained bursting activity, is a major cellular feature of epileptiform activity and antiepileptic drugs acting on voltage‐gated sodium channels were shown to reduce sustained repetitive firing in neurons . We verified that compound A does not modulate TTX‐sensitive voltage‐gated sodium currents (in N1E‐115 neuroblastoma cells; data not shown) further indicating that the molecular mechanism of compound A differentiates from classical antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 67%
“…There is some inconsistency in the reports after levetiracetam intake (also a ligand to the presynaptic vesicle protein SV2A), with some studies reporting an increase in motor threshold (Premoli, Costantini, et al, ; Solinas, Lee, & Reutens, ), while others reported no change (Heidegger, Krakow, & Ziemann, ). The slight increase in motor threshold after BRV intake reported here may relate to a secondary mode of action of BRV in blocking VGSCs (Niespodziany et al, ).…”
Section: Discussionmentioning
confidence: 71%